CsI(Tl) calorimeter with photodiode readout to search for T-violation in K-mu 3 decay - Dementyev, D; Grigorjev, M; Igarashi, Y; Ikeda, T; Imazato, J; Ivashkin, A; Khabibullin, M; Kudenko, Y; Kuno, Y; Mineev, O; Shimizu, S; Watanabe, A; et al. (1996)
A new electromagnetic calorimeter is designed for the experiment E246 at KEK, It consists of 768 CsI(Tl) crystals with PIN-diode readout. A short description of the calorimeter design and performance is given.